The Problematics on Implementation of Law Number 23 Year 2011 Concerning Zakat Management at Baznas Lubuk Linggau City - Aneka Rahma; Badrun Tamam (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
This study aims to explain the problems in implementing Article 3 of Law Number 23 Year 2011 concerning Zakat Management in BAZNAS, Lubuklinggau City, South Sumatra. This is qualitative field and library research. The data collection techniques are observation, interview and documentation. The issues are how the efforts of Baznas Lubuk Linggau in implementing Law Number 23 Year 2011 and what are the problems in its implementation. The results show that Baznas Lubuk Linggau strives to empower zakat funds optimally through the Smart Lubuklinggau Program, Lubuk linggau Peduli, Lubuk linggau Taqwa, Lubuk linggau Sehat, Lubuk linggau Makmur, and Lubuk linggau Amil, as well as proposing a Mayor Regulation on zakat. Meanwhile, the problem of implementation are: the manager does not yet have compelling authority, the institution cannot be controlled by muzakki, supervision of implementation of planned programs is not optimal; lack of awareness of public participation, and the mindset of the people who still think that the zakat funds they receive is a provision and become their right that do not need to be accounted